The role of the first language in hybrid foreign language classes: A sin or a tool? - Colombo, Laura M. (Íkala, Revista de Lenguaje y Cultura, 2012)
The use of the first language (L1) in the foreign language classroom has been highly contested in the last decades. This paper discusses the use of L1 in online activities in hybrid lower-level Spanish as a foreign language (SFL) courses, with a focus on threaded discussions about cultural topics. I first discuss the use of L1 in foreign language (FL) teaching. Second, I present Vygotsky's (1978) postulates about learning, and Cole and Engeström's (2001) activity theory. Third, I conduct an activity analysis of the SFL class to further narrow it down to L1 use in the discussion boards. By looking at the discussion boards through the lens of sociocultural theories, I claim that the use of L1 is a necessary cognitive tool for fostering inter-cultural learning through online discussions in SFL classes.